2020
DOI: 10.1021/acs.biochem.9b01070
|View full text |Cite
|
Sign up to set email alerts
|

Depurination of Colibactin-Derived Interstrand Cross-Links

Abstract: Colibactin is a genotoxic gut microbiome metabolite long suspected of playing an etiological role in colorectal cancer. Evidence suggests that colibactin forms DNA interstrand cross-links (ICLs) in eukaryotic cells and activates ICL repair pathways, leading to the production of ICL-dependent DNA double-strand breaks (DSBs). Here we show that colibactin ICLs can evolve directly to DNA DSBs. Using the topology of supercoiled plasmid DNA as a proxy for alkylation adduct stability, we find that colibactin-derived … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The data implicating colibactin in virulence and colorectal tumorigenesis have motivated extensive structural and pharmacological studies of colibactin (5,(28)(29)(30)(31)(32)(33) and other metabolites of the pks pathway (2,34,35). However, very limited data are available about the regulation of the production of this important genotoxin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data implicating colibactin in virulence and colorectal tumorigenesis have motivated extensive structural and pharmacological studies of colibactin (5,(28)(29)(30)(31)(32)(33) and other metabolites of the pks pathway (2,34,35). However, very limited data are available about the regulation of the production of this important genotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…The warheads of colibactin alkylate DNA on two adenine residues of opposite strands of DNA, which induces a DNA interstrand cross-link (ICL) and ultimately a DNA double-strand break (DSB) ( 4 , 5 ). These types of DNA damage in eukaryotic cells activate DNA repair pathways, resulting in histone H2AX phosphorylation (producing γH2AX) and senescence ( 1 , 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This method was adapted from Xue et al 61 . Here, 1 ml of overnight culture was centrifuged at 1600 g for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Herzon et al deciphered more about the nature of Colibactininduced DNA damage. They concluded that Colibactin induces N3-Adenine alkylations that are depurinated by BER into AP sites, promoting a SSB in each DNA strand and finally DSBs are formed [15,138,139].…”
Section: Colibactinmentioning
confidence: 99%